PEMANFAATAN VIDEO SEBAGAI MEDIA LATIHAN DALAM PEMBELAJARAN BAHASA INGGRIS (Studi Kasus Pada Mata Kuliah Bahasa Inggris II di Kelas Manajemen Informatika AMIK BSI) - Mursyid Kasmir Naserly (Yayasan Akrab Pekanbaru, 2018)
In this study researchers tried to develop a teaching pattern in the basic English language classes. The development of this pattern will focus in the form of exercises using audio visual or video media. Hopefully from this improvement material will arouse the curiosity of the participants, compared to the pattern of text exercises such as multiple choice or commonly found essays. The use of video as an English language training material turned out to be used as a benchmark for the competency of teaching participants, especially in terms of listening, writing and translation. The three aspects of the study were tested simply through a video material that researchers downloaded from youtube.